Case Study of Speech Delay Children at Raudhatul Atfhal Sakinah Kindergarten, Jakarta - Misykah, Zulvia (Cattleya Darmaya Fortuna, 2022)
Education is the right of all human beings, whether children, adolescents, or adults, both girls and boys, both normal children and children with special needs. one example of a child with special needs is a child who has a speech delay, the characteristics of a child who has a speech delay can be known through the pronunciation of words that are always imperfect, not frequently the interlocutor uses sign language when communicating with the child. The problem of speech delays in children is a serious problem, children who have speech delays find it difficult for them to join playmates, even their friends will mock them besides that this will be a mental burden on their parents, not only the child and even the parents. also feel sad about this, because no human being wants to be created with flaws. This study aims to determine: the development of language and speech, (2) how to learn children who have speech delays, (2) find out what factors affect speech delays, (3) and to find out the efforts of teachers and parents in helping a child with speech delays . The approach used in this research is qualitative research. Qualitative research aims to understand the phenomena experienced by research subjects holistically and by means of descriptions in the form of words and language in a special natural context and using various methods